Cerebral Erdheim-Chester Disease Mimicking High-Grade Glial Tumor: A Case Report - DAĞÇINAR, ADNAN; BOZKURT, SÜHEYLA; BAYRİ, YAŞAR (KARGER, 2013)
Erdheim-Chester disease (ECD) is a non-Langerhans histiocytosis. It may present in every organ in the body, but isolated central nervous system involvement, especially a supratentorial intra-axial location, is extremely rare. We present a case of ECD of supratentorial intra-axial origin and discuss the clinical presentation, diagnosis and management strategies. (C) 2014 S. Karger AG, Basel
Keywords: Erdheim-Chester disease; Histiocytosis; Supratentorial intra-axial location; Central nervous system; PROGRESSIVE CEREBELLAR SYNDROME